2019
DOI: 10.1021/acs.jmedchem.8b01946
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Novel Bromophenol–Thiosemicarbazone Hybrids as Potent Selective Inhibitors of Poly(ADP-ribose) Polymerase-1 (PARP-1) for Use in Cancer

Abstract: Poly(ADP-ribose) polymerase-1 (PARP-1) is a new potential target for anticancer drug discovery. A series of bromophenol−thiosemicarbazone hybrids as PARP-1 inhibitors were designed, synthesized, and evaluated for their antitumor activities. Among them, the most promising compound, 11, showed excellent selective PARP-1 inhibitory activity (IC 50 = 29.5 nM) over PARP-2 (IC 50 > 1000 nM) and potent anticancer activities toward the SK-OV-3, Bel-7402 and HepG2 cancer cell lines (IC 50 = 2.39, 5.45, and 4.60 μM), al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 50 publications
2
37
0
Order By: Relevance
“…The results ( Figure 5(B)) suggested that the cell cycle spectrum clearly changed in a dose-dependent manner. However, our result suggested that our degrader arrested the cell-cycle into the G1 phase, while PARP-1 inhibitors generally arrested the cell-cycle into the G2/M phase 37 . The facts that they arrested the cell-cycle into the different phases was attributed to the different mechanisms of inhibitors and degraders.…”
Section: Effect Of 2 On Cell Apoptosismentioning
confidence: 61%
“…The results ( Figure 5(B)) suggested that the cell cycle spectrum clearly changed in a dose-dependent manner. However, our result suggested that our degrader arrested the cell-cycle into the G1 phase, while PARP-1 inhibitors generally arrested the cell-cycle into the G2/M phase 37 . The facts that they arrested the cell-cycle into the different phases was attributed to the different mechanisms of inhibitors and degraders.…”
Section: Effect Of 2 On Cell Apoptosismentioning
confidence: 61%
“…Although few potent compounds have been previously reported [28][29][30]35,43], the anti-TNBC activity of fluoro-thiazolylhydrazone hybrids is reported for the first time in this work. The anticancer activity of TSC-3C for TNBC is evidence for a promising therapeutic agent that is important for drug discovery and clinical applications.…”
Section: Introductionmentioning
confidence: 85%
“…Halogenated compounds come from various sources, such as natural marine products [19], and have diverse potent activities, including antidiabetic [20], antimicrobial [21], antioxidative [22], anti-inflammatory [23], and anticancer activities [23][24][25][26][27]. In our previous work, a series of bromophenol hybrids with active anticancer moieties were designed and synthesized as potential anticancer agents [28][29][30]. The chloro-thiazolylhydrazone compound 4EGI-1 is an inhibitor that has been reported to have a structure-activity relationship (SAR) and anticancer activity [31,32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bromophenol-thiosemicarbazone hybrid was a kind of novel synthetic brominated anticancer compound, with two bromine atoms. Pharmacological results showed that bromophenol-thiosemicarbazone hybrid showed considerable better inhibitory activity of PARP1 (IC 50 = 29.5 nmol/ L) (Guo, wang et al 2019). Generally, most naturally occurring bromine consists of a mixture of two stable isotopes: 79 Br and 81 Br (Heumann, Smith et al 1998).…”
Section: Introductionmentioning
confidence: 99%